2009
DOI: 10.1017/s1368980009990668
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Missouri WIC (Special Supplemental Nutrition Program for Women, Infants, and Children) breast-feeding peer counselling programme

Abstract: Objective: To evaluate the effectiveness of the peer counselling (PC) programme on breast-feeding initiation among participants in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) in Missouri, and to identify factors that facilitate breast-feeding initiation.Design: We used the data from the 2006 Missouri Pregnancy Nutrition Surveillance System, Missouri Live Birth Records and the Missouri WIC programme to compare breast-feeding initiation rates between PC and non-PC agencies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 12 publications
0
27
1
Order By: Relevance
“…29,34,35,[37][38][39][80][81][82][83][84][85][86][87][88][89] Nine interventions were delivered in the USA, all associated with the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). [80][81][82][83][84][85][86][87]89 Five papers related to UK-based interventions 34,35,[37][38][39]88 and one intervention was delivered in Canada. 29 Studies were included if they pertained to a model of BFPS that included planned one-to-one contact between a mother and a peer supporter, reported breastfeeding rates (initiation, continuation or exclusivity) as an outcome measure and if they had been delivered in a developed country setting.…”
Section: Rapid Evidence Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…29,34,35,[37][38][39][80][81][82][83][84][85][86][87][88][89] Nine interventions were delivered in the USA, all associated with the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). [80][81][82][83][84][85][86][87]89 Five papers related to UK-based interventions 34,35,[37][38][39]88 and one intervention was delivered in Canada. 29 Studies were included if they pertained to a model of BFPS that included planned one-to-one contact between a mother and a peer supporter, reported breastfeeding rates (initiation, continuation or exclusivity) as an outcome measure and if they had been delivered in a developed country setting.…”
Section: Rapid Evidence Reviewmentioning
confidence: 99%
“…Eleven studies were RCTs, 29,34,35,37,80,81,84,[86][87][88][89] three were area-based controlled studies 38,82,83 and two were natural experiments. 39,85 Applying Cochrane risk of bias criteria, 91 we found that only three studies had a low risk of bias.…”
Section: Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10][11][12] The common approach in these studies has been to compare the outcomes of WIC clients in LWAs with and without a peer counseling program. 4,5,6,8,12 A systematic literature review of peer counseling initiatives has characterized many of these observational studies as being of moderate to poor quality. 13 Reviews limited to randomized controlled trials (RCTs) of peer counseling have found that lay support increases exclusive and nonexclusive breastfeeding duration.…”
mentioning
confidence: 99%